End‐Diastolic Forward Flow and Restrictive Physiology in Repaired Tetralogy of Fallot: A Systematic Review and Meta‐Analysis - Jef Van den Eynde; Emilie Derdeyn; Art Schuermans; Pushpa Shivaram; Werner Budts; David A. Danford; Shelby Kutty (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Pulmonary arterial end‐diastolic forward flow (EDFF) following repaired tetralogy of Fallot has been thought to represent right ventricular (RV) restrictive physiology, but is not fully understood. This systematic review and meta‐analysis sought to clarify its physiological and clinical correlates, and to define a framework for understanding EDFF and RV restrictive physiology. Methods and Results PubMed/MEDLINE, Embase, Scopus, and reference lists of relevant articles were searched for observational studies published before March 2021. Random‐effects meta‐analysis was performed to identify factors associated with EDFF. Forty‐two individual studies published between 1995 and 2021, including a total of 2651 participants (1132 with EDFF; 1519 with no EDFF), met eligibility criteria. The pooled estimated prevalence of EDFF among patients with repaired tetralogy of Fallot was 46.5% (95% CI, 41.6%–51.3%). Among patients with EDFF, the use of a transannular patch was significantly more common, and their stay in the intensive care unit was longer. EDFF was associated with greater RV indexed volumes and mass, as well as smaller E‐wave velocity at the tricuspid valve. Finally, pulmonary regurgitation fraction was greater in patients with EDFF, and moderate to severe pulmonary regurgitation was more common in this population. Conclusions EDFF is associated with dilated, hypertrophied RVs and longstanding pulmonary regurgitation. Although several studies have defined RV restrictive physiology as the presence of EDFF, our study found no clear indicators of poor RV compliance in patients with EDFF, suggesting that EDFF may have multiple causes and might not be the precise equivalent of RV restrictive physiology.